A research template to evaluate the degree of accountability of integrated reporting: a case study. Issue 4 (2nd October 2017) - Silvestri, Antonella; Veltri, Stefania; Venturelli, Andrea; Petruzzelli, Saverio
Abstract : Purpose: The scope of the study is to analyze an Italian family firm operating in the transformation and marketing of durum wheat to investigate the degree of accountability of the integrated reporting (IR) disclosed by the organization. Design/methodology/approach: The paper uses a case study approach proposing a specific research template to evaluate the implementation of IR depicting the role of three main dimensions: stakeholder involvement, business model and integration. Findings: The paper enriches theoretical conceptualization of the implementation of IR proposing a new conceptual model that adds empirical findings to the literature on IR and at the same time addresses the call for studies of Dumay et al. (2016) to engage more with practice and development on IR. Research limitations/implications: The use of a specific research framework constitutes both the main strength of the paper and also its main limit, as the dimensions of the framework have been chosen by the authors, and the observations and conclusions are based on the authors' analysis under an interpretative approach. Practical implications: The implementation of the same research framework to other organizational IR documents could allow comparisons to be expressed on the quality of the IR disclosed by different organizations and on the same organization in different periods of time. Originality/value: The main originality of this paper is the creation and the employment of a specific template to analyze the degree of accountability of the case study selected representing a non-listed Italian company operating in the food industry.